The Relationship Between PAI Teacher Motivation and Student Learning - Nurul Eka Safitri; Sukari Sukari; Sugiyat Sugiyat (Edumaspul: Jurnal Pendidikan, 2023)
Education is a conscious and systematic work for students to actively acquire intelligence, skills, and adaptability. The Education Process can make students think and remember by Encouraging student creativity to create useful things If you support these student activities, you can develop the potential that exists in every student and can make a difference in knowledge, skills, and behavior. The purpose of this study was to determine the relationship between the motivation of PAI teachers and students' learning interest in the subject of Aqidah Akhlak Class VIII MTS Negeri 5 Sragen. This study uses the quantitative correlation method, a method aimed at finding relationships between at least two parts of the variable. The results of this study indicate that the correlation model of Islamic religion teacher motivation between students' learning interests and student learning outcomes in the Aqidah Akhlak subject is given by the correlation coefficient. r = 0.983 and the coefficient of determination is R = r2 = 0.967. Testing the significance of the correlation was determined by Tcount (37.8 ) > Ttable (1.675) with α = 0.05. This calculation shows that there is a relationship between the motivation of PAI teachers and student's interest in learning with the learning outcomes of Aqidah Akhlak class VIII MTS Negeri 5 Sragen.